2006
DOI: 10.1021/jp0617625
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of the Ionization of the DNA Bases:  Ionization Potentials and Excited States of the Cations

Abstract: The ionization of the four DNA bases is investigated by means of ab initio calculations. Accurate values of the gas-phase vertical and adiabatic ionization potentials (IP) are obtained at the MP2/6-31G(2d(0.8,alpha(d)),p) level of theory. The need of introducing extra polarization to the standard 6-31G(d,p) basis set is demonstrated by test calculations and an optimal value of alpha(d) = 0.1 is obtained. Ionization to electronically excited radical cations is also considered. The low-lying excited states of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
86
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 63 publications
11
86
0
Order By: Relevance
“…Table 3, ROMP2/6-311++G**). Similar trends were obtained by Cauët et al 39 We still keep the exception of o-tolualdehyde ranging outside the mentioned error regime, i.e., 0.35 eV error.…”
Section: Methods Comparison For the Calculation Of Adiabatic Ionizatiosupporting
confidence: 88%
See 1 more Smart Citation
“…Table 3, ROMP2/6-311++G**). Similar trends were obtained by Cauët et al 39 We still keep the exception of o-tolualdehyde ranging outside the mentioned error regime, i.e., 0.35 eV error.…”
Section: Methods Comparison For the Calculation Of Adiabatic Ionizatiosupporting
confidence: 88%
“…The separation of the geometry optimization and the energy calculation, treated each by two different methods, has been used with success in the past. [39][40][41][42] 3.2. Heats of Formation.…”
Section: Methodsmentioning
confidence: 99%
“…9,[15][16][17][18] Trofimov et al 9 measured a valence-shell PES of cytosine. By analyzing photoelectron energy and angular distributions, they concluded that only one tautomer, C2b (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Ab initio calculations of the IE's of the biologically relevant tautomer of cytosine have been reviewed by Roca-Sanjuan et al 16,17 and Cauet et al 17 Other tautomers were considered by Wolken et al who estimated the lowest IEs by DFT, MP2 and CCSD(T) calculations. 15 More reliable values of valence-shell VIEs of the five lowest-energy tautomers obtained using electron propagator methods were reported by Ortiz and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However, previous single-photon ionization (SPI) studies of guanine have all been conducted utilizing the thermal vaporization method. Hush and Cheung, 15 using photoelectron spectroscopy (PES), reported a vertical ionization energy (VIE) of 8.24 eV.…”
mentioning
confidence: 99%